Cultivating an Ethical School. - Starratt, Robert J. (Taylor & amp; Francis, 2012)
Often the school is left as an institution seemingly ethically neutral, leaving untouched questions about whether the school itself is a site of injustice toward both educators and children. Springing from his well-known Building an Ethical School, Robert J. Starratt now looks more closely at the educational leader's responsibility to ensure that the whole fabric of the educational process reflects an ethical philosophy of education. Starratt argues that the work of educating young people is by its very nature an ethical work as well as an intellectual work, and that this work inescapably enga.